On the field fluctuations in a random dispersion - Ilieva, Keranka; Markov, Konstantin (Ann. Sofia Univ. Fac. Math. and Inf., 1999)
In this note the variances of the basic random fields - temperature and heat flux - in a dilute dispersion of spheres with a small volume fraction c 1, subjected to a constant macroscopic temperature gradient are studied. The basic result is an estimate on the c^2-term of these variances, which includes the well-known c^2-term of the effective conductivity, extensively studied in the literature.